Acute Hepatocellular Drug Induced Liver Injury Probably by Alfuzosin - Tufan Cicek; Huseyin Savas Gokturk; Gulhan Kanat Unler (Case Reports in Urology)
Alpha blockers are the drugs that exert their effects by binding to alpha receptors and relaxing smooth muscles and are currently used for treatment of benign prostate hyperplasia (BPH). These drugs are often tolerated well by the patients. However, they also possess some common side effects. Hepatotoxicity, on the other hand, is quite rare. We report herein a case with the rare complication of acute hepatocellular drug induced liver injury (DILI) by administration of Alfuzosin.